PERBEDAAN PENGETAHUAN REMAJA TENTANG SEKS BEBAS DI SMA PERKOTAAN DAN PEDESAAN KABUPATEN KUDUS - Kudarti Kudarti; Theresia Catur Wulan Setyaningrum; Ikasari Kristiani (Jurnal Riset Kesehatan, 2016)
Lack of understanding of sexual behavior in adolescence is very harmful for young people themselves, including their families, because at this stage. Based on age, adolescents aged 10-19 years as many as 135 846 which partly was in high school. This study was an observational study with cross sectional approach. The sampling technique used was cluster random sampling. Analysis of the data used is the comparative test using independent t test to determine differences in tilapia averaged between one group against another unrelated. Data processing is done by univariate and multivariate analysis. This study obtained a result that students' knowledge about sex in high school at 83.42 and in the Urban Rural High School at 81.26, so it can be the difference between the two high school knowledge is 2, 16. And when viewed from different test p value between two high school proficiency level shows that the p value of 0.000. Value indicates less than 0.05, so it can be concluded that there is a difference between high school students' knowledge of urban and rural high school students in the district of Kudus.